Penerapan Struktur Paralel pada Penulisan Skenario Video Feature “Ibu untuk Bumi” - Leyda Kusumadinata; Toto Sugito; Andri Yanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This paper explains the implementation of the creation of a screenplay for a feature video entitled "Mother for the Earth" with a focus on the application of parallel structure in four scenes: teaser, conflict, climax, and catharsis. Each scene serves to build narrative tension, strengthen the central theme, and generate a deeper understanding of the importance of environmental awareness. The parallel structure is applied to show a strong contrast between two mothers with different lifestyle backgrounds—one mother who adopts an environmentally friendly lifestyle and the other mother who is less concerned with life's desires. In the teaser scene, the scenario presents two main characters living in different worlds, arousing the audience's curiosity about the differences in the two mothers' views and attitudes towards the world around them. In the conflict scene, both face challenges and dilemmas related to their chosen lifestyles. The climax scene shows the culmination of their conflict, while the catharsis scene provides a resolution, where one of the mothers finally realizes the importance of small changes in daily habits that can have a big impact on the environment. This work aims to educate the audience, especially families and housewives, about the importance of raising environmental awareness from an early age in children. Through the use of parallel structure, the message about simple behaviors that have a significant impact on the environment becomes more powerful and compelling, inspiring the audience to take positive action in their daily lives for a better planet. The use of parallel structure in this scenario also serves to demonstrate how the two mothers, despite coming from different backgrounds, can share the same goal of preserving the earth.